2022
DOI: 10.1186/s12876-022-02272-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan intermittent fasting on inflammatory markers, disease severity, depression, and quality of life in patients with inflammatory bowel diseases: A prospective cohort study

Abstract: Background Intermittent fasting (IF) during the month of Ramadan is part of the religious rituals of Muslims. The effect of intermittent fasting on disease activity in inflammatory bowel diseases (IBD) is still unknown. This is the first study to assess the effect of IF during Ramadan on inflammatory markers in patients diagnosed with IBD. The effects on clinical disease activity, quality of life, and levels of depression were also assessed. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
(49 reference statements)
0
16
0
5
Order By: Relevance
“…However, Negm M et al recruited 80 patients with IBD to observe the effect of Ramadan intermittent fasting on disease activity, which is part of the religious rituals of Muslims. They found that the Mayo score had significantly risen after intermittent fasting, especially in older patients and those with higher baseline calprotectin levels, but serum CRP and stool calprotectin did not change significantly before vs. after fasting [ 176 ]. The therapeutic potential of intermittent fasting on IBD needs more human studies.…”
Section: Dietary Strategies Alleviating Ibdmentioning
confidence: 99%
“…However, Negm M et al recruited 80 patients with IBD to observe the effect of Ramadan intermittent fasting on disease activity, which is part of the religious rituals of Muslims. They found that the Mayo score had significantly risen after intermittent fasting, especially in older patients and those with higher baseline calprotectin levels, but serum CRP and stool calprotectin did not change significantly before vs. after fasting [ 176 ]. The therapeutic potential of intermittent fasting on IBD needs more human studies.…”
Section: Dietary Strategies Alleviating Ibdmentioning
confidence: 99%
“…in older patients and these may have contributed to changes in the physician's assessment portion of the PMS. 9 Reasons for why these results differ somewhat from those in the studies of rheumatic diseases 12,13 are speculative in the absence of other published literature but could be related to effects on the gut microbiome, autophagy, and other similar pathophysiologic mechanisms that underpin IBD and other immune-mediated diseases.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 84%
“…The effects on clinical disease activity, quality of life, and levels of depression were assessed. 55 Patients diagnosed with ulcerative colitis (UC) or Crohn's disease (CD) intending to observe RF were recruited. The following were assessed immediately before and at the end of Ramadan: serum CRP and stool calprotectin, partial Mayo score, Harvey-Bradshaw index (HBI), Simple IBD questionnaire (SIBDQ), and Hamilton depression scale questionnaire.…”
Section: Gut and Livermentioning
confidence: 99%